Optimal Design of Block Quay Walls - Francois, Stijn; Lesage, Louis; Verbraken, Hans; Schevenels, Mattias (Frontiers in Built Environment, 2020)
Block walls, consisting of stacked unreinforced prefabricated concrete blocks, are commonly used for the construction of quay walls in the presence of rocky subgrades. A traditional design of block quay walls is based on manual design iterations, envisaging sufficient safety against ultimate limit states (ULS) such as sliding, overturning or loss of bearing capacity of the foundation soil. In addition, the designer should consider stability during the different construction stages of the block wall, referred to as buildability constraints. This design process can be laborious, while the resulting designs comprise a large volume of concrete. In order to optimize block quay walls, we developed an automated design procedure in the framework of gradient-based optimization, accounting for the various ULS and buildability constraints encountered in engineering practice. The design checks for a block quay wall are first explained in detail. This includes global ULS requirements that apply to the block wall as a whole, and internal ULS requirements to consider sliding and overturning of separate blocks. During construction, the block wall has to be stable during all construction stages, which imposes additional design constraints. Next, block walls consisting of rectangular blocks and chamfered blocks are optimized. The resulting designs obtained with the automated design procedure satisfy all design requirements, and have a realistic layout. Furthermore, the influence of the different construction stages is studied, demonstrating the practicality of the proposed automated design procedure.